2019
DOI: 10.3390/molecules24224187
|View full text |Cite
|
Sign up to set email alerts
|

NAD Analogs in Aid of Chemical Biology and Medicinal Chemistry

Abstract: Nicotinamide adenine dinucleotide (NAD) serves as an essential redox co-factor and mediator of multiple biological processes. Besides its well-established role in electron transfer reactions, NAD serves as a substrate for other biotransformations, which, at the molecular level, can be classified as protein post-translational modifications (protein deacylation, mono-, and polyADP-ribosylation) and formation of signaling molecules (e.g., cyclic ADP ribose). These biochemical reactions control many crucial biolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 99 publications
(137 reference statements)
0
21
0
5
Order By: Relevance
“…While we could use the GAP-tag to site-specifically label proteins with ADP-ribose, we sought to demonstrate that this system could be extended with NAD + analogs to introduce various chemical groups to the C-terminus of proteins. Many NAD + analogs already exist and are commercially available such as biotinylated, fluorescent and click-chemistry ready NAD + analogs (Depaix and Kowalska, 2019). We first tested the modification of GAP-tagged YFP with 6-biotin-17-NAD + and confirmed that this NAD + analog serves as substrate for PT-based modification of the GAP-tag (Figure 3a).…”
Section: The Gap-tag For Site-specific Labelling Of Proteins Using Nad + Analogsmentioning
confidence: 79%
“…While we could use the GAP-tag to site-specifically label proteins with ADP-ribose, we sought to demonstrate that this system could be extended with NAD + analogs to introduce various chemical groups to the C-terminus of proteins. Many NAD + analogs already exist and are commercially available such as biotinylated, fluorescent and click-chemistry ready NAD + analogs (Depaix and Kowalska, 2019). We first tested the modification of GAP-tagged YFP with 6-biotin-17-NAD + and confirmed that this NAD + analog serves as substrate for PT-based modification of the GAP-tag (Figure 3a).…”
Section: The Gap-tag For Site-specific Labelling Of Proteins Using Nad + Analogsmentioning
confidence: 79%
“…Pellagra is a dermatitis, diarrhea, and dementia related disease that occurs as a result of dietary deficiency of niacin and vitamin B3 compounds (Orlandi et al 2017 ; Sahar et al 2011 ). There have been elaborate studies on how this molecule relates to aging (Braidy and Liu 2020 ; Yoshino et al 2018 ; Depaix and Kowalska 2019 ), thus positioning it as a major universally conserved age-dependent biomolecule. Upon decline of NAD, cell aging ensues owing to the damaging effects of accumulated toxic molecules.…”
Section: Overview Of Nad: An Essential Cofactor In Biological Systemmentioning
confidence: 99%
“…ARTD11 targets NXF1 (an mRNA-binding protein involved in the nucleocytoplasmic shuttle) and NUP98, while modification of NAGK is dependent on the WWE domain present in the ARTD11/PARP11 enzyme [ 119 , 120 ]. ITK7, a quinazolin-4(3H)-one scaffold with propynyl in R1 and pyrimidine in R2 substitutions, showed high specificity toward ARTD11, whose activity towards nuclear pore complex proteins leads ARTD11 to dissociate from the nuclear envelope [ 121 ].…”
Section: Mono(adp-ribosyl) Transferases (Mart)mentioning
confidence: 99%
“…The nuclear transport protein RAN is also an ARTD10 substrate [ 87 ]. WRIP1 protein was used as a dual ARTD10/ARTD11 MARylation target in cell extracts [ 119 , 120 ].…”
Section: Mono(adp-ribosyl) Transferases (Mart)mentioning
confidence: 99%